2021
DOI: 10.3390/polym13121915
|View full text |Cite
|
Sign up to set email alerts
|

Non-Newtonian Droplet Generation in a Cross-Junction Microfluidic Channel

Abstract: A two-dimensional CFD model based on volume-of-fluid (VOF) is introduced to examine droplet generation in a cross-junction microfluidic using an open-source software, OpenFOAM together with an interFoam solver. Non-Newtonian power-law droplets in Newtonian liquid is numerically studied and its effect on droplet size and detachment time in three different regimes, i.e., squeezing, dripping and jetting, are investigated. To understand the droplet formation mechanism, the shear-thinning behaviour was enhanced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
9
15
0
Order By: Relevance
“…Under the qualitative point of view (Figure 2a), for the same set of imposed volumetric flow rate values, the droplet size did not differ significantly between Newtonian and non-Newtonian droplets, in agreement with previous finding on viscoelastic droplet microfluidics. 15,16,[28][29][30][31][32][33][34] However, we observed a clear difference in the dynamics of droplet formation between Newtonian and non-Newtonian droplets, with the presence of satellite droplet formation only observed for the non-Newtonian case, in agreement with previous findings featuring formation of viscoelastic droplets made of aqueous xanthan gum solutions in a commercial T-junction device. 15 We also quantified the droplet length L normalised by the channel width W = 100 µm, as a function of the ratio between the flow rate of the dispersed and the continuous phase (Figure 2(b-c)).…”
Section: Droplet Formationsupporting
confidence: 91%
See 2 more Smart Citations
“…Under the qualitative point of view (Figure 2a), for the same set of imposed volumetric flow rate values, the droplet size did not differ significantly between Newtonian and non-Newtonian droplets, in agreement with previous finding on viscoelastic droplet microfluidics. 15,16,[28][29][30][31][32][33][34] However, we observed a clear difference in the dynamics of droplet formation between Newtonian and non-Newtonian droplets, with the presence of satellite droplet formation only observed for the non-Newtonian case, in agreement with previous findings featuring formation of viscoelastic droplets made of aqueous xanthan gum solutions in a commercial T-junction device. 15 We also quantified the droplet length L normalised by the channel width W = 100 µm, as a function of the ratio between the flow rate of the dispersed and the continuous phase (Figure 2(b-c)).…”
Section: Droplet Formationsupporting
confidence: 91%
“…We observed that the data for viscoelastic droplet formation scaled with the same scaling as the Newtonian ones, thus suggesting that the droplet size is not affected by the fluid rheology significantly, in agreement with previous works. 15,16,[28][29][30][31][32][33][34] We also observed that the frequency of droplet generation scaled as f d = A (Q HA Q oil ) B with 6/9 A = 1.64 ± 0.18 and B = 2/3. The parameter A was obtained by fitting the entire data set with flow rate values in the units of µL/min, while B was fixed to B = 2/3 according to the previously introduced by Shahrivar and Del Giudice 15 for xanthan gum solutions.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In other words, the fact that the data followed the scaling for Newtonian droplets may indicate that the droplet size is not significantly affected by the fluid elasticity. We observed a similar phenomenon in our recent work featuring viscoelastic droplets in Tjunction microfluidic devices [25], thus suggesting that fluid viscoelasticity impacts more the dynamics of droplet formation rather than the final size, agreement with other studies [8,[27][28][29][30][31][32]. Similarly to the droplet size, we also observed that the frequency of droplet formation f d scaled according to a mastercurve dependent upon the flow rate ratio q and the Capillary number Ca (Fig.…”
supporting
confidence: 91%
“…Most of the Si microchannel structures reported at present are in the same layer, in the shape of "T", "Y", comb, cross, Serpentine, and spiral [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. As the feature size of microdevices decreases and the integration degree increases, more complex design and more extended wiring are required in single-layer microchannels, which will affect the efficiency of the device operation.…”
Section: Introductionmentioning
confidence: 99%